Questions kids ask about space and stars - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask About Space and Stars provides captivating answers to children's questions about the universe, helping them explore the wonders of space, planets, and stars in an engaging and educational way.